'Counselling and amplification with and without fractal music (Zen tones) for management of patients suffering from hearing loss and tinnitus'. (2nd January 2018) - Shabana, Mohamed Ibrahim; Dabbous, Abeir Osman; Abdelmajeed, Mohamed Ahmed; Abdelkarim, Ayman Mohamed Mohamed
Abstract: Background: Counselling, stress reduction and sound stimulation have been effective in the management of tinnitus. Aim of the work: It was to investigate the effectiveness of counselling and amplification and sound stimulation (Zen tones of fractal music) technology for hearing impaired patients suffering from tinnitus. Methods: This study included 40 hearing impaired subjects with tinnitus, divided into two groups: Both received counselling for 2 months then amplification for 4 months. The study group had their hearing aids with Zen program activated. Results: Post-counselling, none of the cases or controls showed improvement >20 points in the total tinnitus handicap inventory (THI) score. Only 20% of the study group and 15% of the controls showed improved tinnitus severity. Only one of the study group showed improvement in the tinnitus functional index (TFI) > 13 points. After hearing aids, 80% of the study group showed improvement in the tinnitus severity degree compared to 60% of the controls. And 20% improved ≥20 points in the total THI score, compared to none of the controls. Half of the study group improved in the TFI >13 points, compared to only 10% of the controls, and this was statistically significant. After 6 months, both groups showed comparable improvement in THI tinnitus severity degree: But 60% of the study group and only 15% of the controls improved ≥20 points in total THI score and this difference was statistically significant. And (85%) of the study group improved >13 points in total TFI score following both counselling and hearing aid fitting, compared to 50% of the controls, and this was statistically significant. Conclusion: Counselling alone had no significant effect on tinnitus improvement in the hearing-impaired patients. The combined approach of counselling and amplification resulted in remarkable improvement. And added music resulted in greater improvements, but was more effective when the loudness of the perceived tinnitus was weaker.